2013
DOI: 10.1002/jhet.1777
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biological Evaluation of Novel Benzoxaboroles as Potential Antimicrobial and Anticancer Agents

Abstract: Several novel benzoxaborole derivatives were synthesized starting from 2‐formylphenylboronic acid utilizing Baylis–Hillman reaction, Barbier allylation, Passerini reaction, and aldol reaction protocols as the key step. All the synthesized benzoxaboroles have been evaluated for their antibacterial, antifungal, and anticancer activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Zhang et al described a set of interesting, highly active chalcone-benzoxaborole hybrids [14], but further studies are needed to reveal to what extent the observed activity resulted from the introduction of the boron-containing moiety. Suman et al synthesized a series of 6-aminobenzoxaborole derivatives, of which some showed high antiproliferative activity in pancreatic cancer cells (MIA-PaCa-2) [17], whereas some other examples of 6-aminobenzoxaborole-derived compounds showed no activity in MCF7 at a concentration of 50 μM [40], similarly to a set of β-ketobenzoxaboroles synthesized by Sravan Kumar et al [18]. In both cases, the described compounds had a much more complex chemical structure than the derivatives reported herein.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhang et al described a set of interesting, highly active chalcone-benzoxaborole hybrids [14], but further studies are needed to reveal to what extent the observed activity resulted from the introduction of the boron-containing moiety. Suman et al synthesized a series of 6-aminobenzoxaborole derivatives, of which some showed high antiproliferative activity in pancreatic cancer cells (MIA-PaCa-2) [17], whereas some other examples of 6-aminobenzoxaborole-derived compounds showed no activity in MCF7 at a concentration of 50 μM [40], similarly to a set of β-ketobenzoxaboroles synthesized by Sravan Kumar et al [18]. In both cases, the described compounds had a much more complex chemical structure than the derivatives reported herein.…”
Section: Discussionmentioning
confidence: 99%
“…In the studies by Plopper et al [15] and Marasovic et al [16], phenylboronic acid showed limited activity in prostate and mammary gland cancer models. Some benzoxaborole-derived compounds, such as 6-aminobenzoxaboroles, exhibited interesting antiproliferative activity [17], whereas some other derivatives such as β-ketobenzoxaboroles showed no such potential [18]. Herein, for the first time, we provide comprehensive evidence for the high anticancer potential of such compounds using several diverse cancer cell lines that cover a spectrum of malignancies that are currently commonly diagnosed in humans: leukemia (MV-4-11), breast (MCF7), urinary bladder (5637), ovarian (A2780) and lung cancer (A-549).…”
Section: Introductionmentioning
confidence: 99%
“…However, an investigation of their anticancer activity has been lacking to date. Although several preliminary efforts toward this goal have been reported, the anticancer activity of benzoxaboroles has not been convincingly defined in those studies. ,, We have previously reported a small group of chalcone–benzoxaborole hybrids as preliminary anticancer agents . Here, we report the design, synthesis, and structure–activity relationship of a series of 7-propanamide benzoxaboroles with potent anticancer activity.…”
Section: Introductionmentioning
confidence: 92%
“…Reaction of 2-formylphenylboronic acid with isonitriles results in α-amidobenzoxaboroles ( 517 – 519 , Scheme ; 520 – 525 , Figure ) . Several 3-substituted benzoxaboroles have been obtained in the reaction with α-bromomethyl acrylates ( 526 – 529 , Scheme ; 530 – 547 , Figure ). , Recently, also a method for the synthesis of 3-indolyl-substituted benzoxaboroles starting from 2-formylphenylboronic acid has been developed ( 548 – 558 , Scheme ) …”
Section: Synthesis Of Benzoxaborolesmentioning
confidence: 99%
“…Aldol reaction of 2-formylphenylboronic acid with methyl ketones or malonic esters resulted in several benzoxaborole-containing carbonyl compounds ( 548 – 554 , Figure ) . The authors claimed that the studied 3-substituted benzoxaboroles displayed no antibacterial, antifungal, antitubercular, or anticancer activity.…”
Section: Synthesis Of Benzoxaborolesmentioning
confidence: 99%